Whole fruit pulp (mango) and a soluble fibre (pectin) impact bacterial diversity and abundance differently within the porcine large intestine. (July 2019) - Grant, Lucas J.; Mikkelsen, Deirdre; Ouwerkerk, Diane; Klieve, Athol V.; Gidley, Michael J.; Williams, Barbara A.
Abstract: Effects of diets including a fruit cell-wall matrix (mango) or a soluble cell-wall polymer (pectin), on the porcine large intestine (LI) bacterial community were examined at the caecum (Cae), proximal (PC), mid- (MC), and distal colon (DC), investigating both bacterial composition and metabolic end-products. Pigs were fed one of three diets: Control based on wheat starch, and treatment diets where starch was partially substituted with either 15% mango pulp or 10% pectin. Fermentation end-products were significantly different between diets, and LI sites (P < 0.001). Control-diet fed pigs had lowest SCFA and highest ammonium concentrations. Distally, SCFA concentrations decreased across all diets, resulting in reduced differences between diets. The more complex fibre in the Mango diet promoted increased bacterial diversity within the Cae and PC, compared with pigs fed the Control and Pectin diets. At each site, the order of total species abundance and diversity was Mango > Control > Pectin. Between diet groups, there were distinct community differences. Species abundance that differed per diet included Faecalibacterium prausnitzii (Pectin), and Lactobacillus mucosae (Mango). However, Mango promoted a more stable abundance of F. prausnitzii along the LI, while Pectin resulted in F. prausnitzii abundance being high proximally and low distally. This contrasted with the low fibre Control diet results, where F. prausnitzii was not detectable. This study has shown that although pectin can promote extensive fermentation early in the LI, more prolonged and beneficial effects in the distal LI, including greater microbial species diversity, occur when the diet includes plant material with complex intact plant cell-walls, such as from mango. Graphical abstract: Image 1 Highlights: Mango diet was associated with greater bacterial diversity in the large intestine (LI) and promoted increased SCFA concentrations in LI digesta, particularly proximally. Each diet was associated with distinctive bacterial communities. Mango diet promoted stable Faecalibacterium prausnitzii levels across LI sites. Pectin-diet levels of F. prausnitzii decreased towards the distal LI. Mango-diet associated with the presence of Lactobacillus mucosae.